The Politeness of Strategies Used by Students STKIP PGRI Trenggalek - Susanto; Yahmun (Universitas Insan Budi Utomo, 2023)
This study purpose to analyze the politeness strategies used by English Study Program. The student is seven semesters in study process. In completing this research, the researcher used a qualitative descriptive method and the theory of Brown and Levinson. From this study, the researcher found four kinds of politeness strategies used by the English Study Program; those are bald on record, positive politeness, negative politeness and Off-record. The factors that influence the politeness strategy used by the main are the payoffs and social variables. Furthermore, sociological variables also affect the use of politeness strategies used by students, which are social distance, relative power and rank of imposition. The suggestion to the next researcher is able to investigate more about politeness in a broader context and combine it with other social aspects such as religion, ideology, or even culture.